KENDALA DALAM MENGIMPLEMENTASI KEBIJAKAN PEMUNGUTAN PAJAK RUMAH KOST DI KELURAHAN SEI BANGKONG KECAMATAN PONTIANAK KOTA - Anugrah E.21110102, Nunu (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Opened as a boarding house for the purpose of business is the right of every citizen, all the rights set out in the Act. But as we all know that any rights then there is liability. And this also applies to citizens who want to build a building for the purpose as a place of business should be to meet obligations that have been established to complete its de. But in fact the level ofÂ  awareness of the tax payer to pay the tax in the boarding house boarding house are low so the target cannot be met. Then the level of adherence to licensing boarding community is still low. The focus of there search is trying to discuss using qualitative methods with case studies in the Village District Sei Bangkong, Pontianak City. This study is a illustrate show the implementation of the Regional Regulation No. 6 of 2010 on local taxes in particular boarding house. the results of this study is that the implementation of the Regional Regulation No.6of 2010 on local taxes are particularly constrained and boarding house tax has not gone up due to communication factors, resource factors, factors and factor structure of bureaucratic disposition. To there commendation of the authors that empha size the penalties for not paying taxes in accordance with the regulation No. 6 of 2010 on local taxes in particular tax boarding house.Keywords: Boarding House Tax, Tax Pay Awareness, Dissemination Policy